Sol gel transition of konjac glucomannan - M. B., Siti Aisyah; Mat Hashim, Dzulkifly; Mustafa, Shuhaimi (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
Konjac glucomannan (KGM) is a high molecular weight plant found in tubers of the Amorphophallus konjac. Due to adulteration of porcine gelatine in pharmaceutical products, KGM obtained an ideal characteristic which can be developed as substitute to gelatine. The transition from the liquid state (sol) to the solid state (gel) is called the sol-gel transition and the critical point for the transition is defined as the gel point. To study a gelling material, it is important to have a method to determine the gel point in an accurate and reproducible manner.